2022
DOI: 10.1177/20413866221133669
|View full text |Cite
|
Sign up to set email alerts
|

Finally, some “me time”: A new theoretical perspective on the benefits of commuting

Abstract: Most research on commuting has focused on its negative aspects and consequences (i.e., stress). However, some work has also begun to recognize that there may be positive aspects to commuting. In this paper, we develop a perspective that has so far received limited attention, highlighting how the commute can be experienced as desired and beneficial “me time”, due to the fact that it inhabits a “third space” that is less associated with work or home role requirements. Drawing upon and integrating theories and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Just like the data of Nikolaeva et al (2022), our respondents demonstrated that the commute demarcates a transition between work and home; without commuting this separation has vanished. Pindek et al (2022) emphasised that the commute may have positive aspects, which is similar to the interviewees' statements about "me time". The quality of "me time" is more important than quantity, as participant C stated.…”
Section: Discussionsupporting
confidence: 56%
“…Just like the data of Nikolaeva et al (2022), our respondents demonstrated that the commute demarcates a transition between work and home; without commuting this separation has vanished. Pindek et al (2022) emphasised that the commute may have positive aspects, which is similar to the interviewees' statements about "me time". The quality of "me time" is more important than quantity, as participant C stated.…”
Section: Discussionsupporting
confidence: 56%
“…More recently, research has investigated the beneficial aspects of commuting and bidirectional spillover relationships between commuting and work (Calderwood & Mitropoulos, 2021; Wiese et al, 2020b). For example, commuting has been found to provide opportunities for refreshment and role transitions (Jachimowicz et al, 2021; Pindek et al, 2023). Thus, the interrelations between employees’ commuting and work experiences can be ambivalent, influenced by a variety of factors (Wiese & Calderwood, 2022).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Other papers make this point a central aspect of their contribution. For example, Pindek et al (2022) propose that commuters can use the time they are traveling to and from work as “Me Time,” where they recover from their experiences in their previously occupied domain and replenish crucial personal resources that may be depleted by working. Gerpott et al (this issue) break down the psychological aspects of the commuting experience in explaining when the commute positively or negatively affects experiences in the commuter's subsequently occupied domain (e.g., work, home).…”
Section: Challenging the Status Quomentioning
confidence: 99%
“…Another shared theme across these articles is the role of time. Several authors noted the need to examine the commuting experience using intensive longitudinal methods (Fruhen et al, this issue; Murphy et al, 2022; Nolan et al, this issue; Pindek et al, this issue). Longitudinal methods are critical within commuting research as these experiences naturally fluctuate daily (e.g., commuting times, conditions, and experiences may change substantially from day-to-day), and the impact of this commuting variability can have both shorter- and longer-term consequences.…”
Section: The Future Of Commutingmentioning
confidence: 99%
See 1 more Smart Citation